A Review on Cash Waqf for Education in Malaysia: Challenges and Impacts - Wan Hasanah Megat Ajib (Universitas Ahmad Dahlan, 2022)
Introduction: The cash waqf has been practiced widely since the beginning of the 15th Century during the reign of the Ottoman Empire and The Fatwa Committee of the 77th National Council for Islamic Religious Affairs Malaysia announced its permissibility in Malaysia on 12 April 2007. Since that, the cash waqf is developed rapidly and most of the collection is focused on educational purposes. This study identifies the challenges and impacts of cash waqf in Malaysia specific for education. Purpose: This study identifies the challenges and impacts of cash waqf in Malaysia specific for education. Methodology: This study used a descriptive method based on previous studies, secondary data from the published book, and regulatory bodies’ official portals. Findings: The findings showed four main challenges faced by the waqf authority; (1) lack of expertise by the waqf staff and manager in cash waqf management; (2) low level of public awareness and less understanding of the university’s top management; (3) inconsistency of enactments because of the state’s enactment; (4) Improper documentation and no publication on the latest annual report. Despite the challenges, the implementation of cash waqf contributed more good impacts on students and educational institutions such as (1) improve the facilities of schools and universities, (2) more university waqf centers had been established, (3) the welfare of disabled and poor students is guaranteed, and (4) enrich the quality of higher education through research grants.